Development of fish meat sheets from milkfish (Chanos chanos, Forskal) deboning wastes - Balsamo, Gernimo Tingzon (2007.)
A study on the development of a processing method for the production of milkfish meat sheets, a new fishery product from deboning wastes, was conducted using the recovered flesh from milkfish frames/backbones. A series of trials were done to develop a single processing method to come up with a product that is in sheet form, shelf-stable, acceptable to the consumers and uses the processing wastes from deboning of milkfish. Different treatments and trials conducted have identified that washing and brine concentration as the most critical steps which affect the texture. Based on the results of the sensory evaluations, the treatments significantly affected the texture of the product. A1B2 was the most preferred by the panelists, which was washed two times and mixed with 1% brine. Acceptability scores for color and aroma were not significantly different from each other in all the treatments. Flavor acceptability scores were significantly affected by brine soaking and the most acceptable were A1B2 and A2B2, which were jinxed with 1% brine. Soaking in 0% brine solution (A1B1 and A2B1) is the least susceptible to halophilic organism; while treatments which were mixed with 1% brine (A1B2 and A2B2) were the least susceptible to mold growth. Based on the physico-chemical analyses, washing and brine soaking significantly affected the product. Number of washing was directly proportional to the moisture and salt contents but inversely proportional to the protein and lipid contents. The rehydration ratio, which is an indicator of the texture quality of the dried product, revealed that A2B2 was the best treatment. In addition, washing dd ot affect the rehydration ratio of the dried product. The treatments had no significant effect on pH of the final product. The average pH value was 7. Aw showed that all the treatments may possibly spoil due to lipid oxidation, non-enzymatic browning and hydrolytic reaction but not by microbial activities. The drying rate is directly related to the concentration of brine soaking. This phenomenon is attributed to the initial moisture content of the samples. Generally, A1B2 is the best treatment among the treatments done based on the developmental objectives specified on the study.
Thesis (Bachelor of Science in Fisheries major Fish Processing Technology) Institute of Fish Processing Technology, College of Fisheries and Ocean Science, University of the Philippines Visayas, 2007.
Keywords: Fish meat sheets; Milkfish; Chanos chanos Forskal; Deboning wastes